The Position of Islamic Law in Fulfilling Women's Rights during the Iddah Period - Sitompul, Kristina Pujasari; Simbolon, Nur Anisa; Rifai, Muhammad; Hadiningrum, Sri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
According to the language, the word iddah comes from the word’ ada (number, ihshaak, and calculation), a woman who counts and sums the days and periods of menstruation of the holy period. The purpose of this study to determine how the position of Islamic law in the fulfillment of women's rights during iddah, what are the problems in the fulfillment of women's rights during iddah, and how solutions to overcome problems in the fulfillment of women's rights during iddah. The method of writing this article uses literature research, which is a method of collecting data by understanding and studying theories from various literature related to research. The results showed that violations of the iddah period are often committed by women who file for divorce, generally the cause of divorce is motivated by several factors, namely, low public education, economic conditions, quarrels, infidelity and domestic violence.